Flavonoids with gastroprotective activity - De Lira Mota, Kelly Samara; Dias, Guilherme Eduardo Nunes; Pinto, Meri Emili Ferreira; Luiz-Ferreira, Ânderson; Souza-Brito, Alba Regina Monteiro; Hiruma-Lima, Clélia Akiko [UNESP]; Barbosa-Filho, José Maria; Batista, Leônia Maria (MDPI, 2009)
Peptic ulcers are a common disorder of the entire gastrointestinal tract that occurs mainly in the stomach and the proximal duodenum. This disease is multifactorial and its treatment faces great difficulties due to the limited effectiveness and severe side effects of the currently available drugs. The use of natural products for the prevention and treatment of different pathologies is continuously expanding throughout the world. This is particularly true with regards to flavonoids, which represent a highly diverse class of secondary metabolites with potentially beneficial human health effects that is widely distributed in the plant kingdom and currently consumed in large amounts in the diet. They display several pharmacological properties in the gastroprotective area, acting as anti-secretory, cytoprotective and antioxidant agents. Besides their action as gastroprotectives, flavonoids also act in healing of gastric ulcers and additionally these polyphenolic compounds can be new alternatives for suppression or modulation of peptic ulcers associated with H. pylori. In this review, we have summarized the literature on ninety-five flavonoids with varying degrees of antiulcerogenic activity, confirming that flavonoids have a therapeutic potential for the more effective treatment of peptic ulcers.
Keywords: Flavonoids; Gastroprotective activity; Natural products.; Peptic ulcers; flavonoid; phenol derivative; polyphenols; protective agent; human; peptic ulcer; review; Humans; Peptic Ulcer; Phenols; Protective Agents